2021
DOI: 10.1002/admi.202101412
|View full text |Cite
|
Sign up to set email alerts
|

Nonwetting Nanostructured Hemostatic Material for Bleeding Control with Minimal Adhesion

Abstract: clotting speed by promoting coagulation reactions. [6,7] However, the commonly used hydrophilic hemostatic materials have the following drawbacks. [7,8] First, they are not effective in bleeding control. As clotting passively depends on the coagulation process, bleeding through the hydrophilic material will not stop until the formation of a strong clot to seal the wound. Second, after clot solidification, the hydrophilic dressing soaked blood would form a composite that strongly adheres on the wound, making it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Reproduced with permission. [ 108 ] Copyright 2021, John Wiley and Sons. b) Illustration and SEM images of fibrin fibers and blood clot formation from blood on a superhydrophobic CNF surface.…”
Section: Wettability and Compatibility Of Sbfrssmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [ 108 ] Copyright 2021, John Wiley and Sons. b) Illustration and SEM images of fibrin fibers and blood clot formation from blood on a superhydrophobic CNF surface.…”
Section: Wettability and Compatibility Of Sbfrssmentioning
confidence: 99%
“…Recently, they also reported another superhydrophobic hemostatic dressing that was prepared by a two‐step spray coating process. [ 108 ] First, the hydrophobic component, beeswax, was sprayed on the surface of the CNFs to form a superhydrophobic nanofibrous structure, and then kaolin particles were decorated on the nanostructure to create a coagulation effect. This superhydrophobic hemostatic dressing exhibited a similar effect as the blood‐repellent CNF/PDMS coating dressing.…”
Section: Application Of Sbfrssmentioning
confidence: 99%
See 2 more Smart Citations
“…Further in vivo assessments demonstrated the gelatin nanofiber sponge’s ability to rapidly induce stabilization of blood clots, thereby leading to the least amount of blood loss compared to other commercialized products currently in use, thus proving its advantage as a hemostatic agent [ 7 ] . Other studies on nanofiber composites have also demonstrated the ability of these structures to promote rapid hemostasis and incur minimal secondary damage due to the composites’ intrinsic property of super-hydrophobicity and high user tunability [ 37 , 83 ] .…”
Section: Micro/nanostructures In Hemostatic Applicationmentioning
confidence: 99%